'Pray for transit': Seeking transportation justice in metropolitan Atlanta. (July 2019) - Karner, Alex; Duckworth, Richard
On 4 November 2014, voters in Clayton County, Georgia, approved a referendum to join the Metropolitan Atlanta Rapid Transit Authority (MARTA), Atlanta's regional transit agency. The historic vote was won by a margin not often seen in US electoral politics – 73% in favour with only 27% opposed. The vote was significant because it resulted from the sustained effort of Clayton County residents, non-profit advocacy organisations and elected officials to replace a public transit service that had been completely eliminated in early 2010. After opting not to join MARTA in 1971, Clayton County became increasingly Black and low-income as the economic centre of Atlanta shifted northwards. This demographic transition made public transit a necessity, and a bus service began in the county in 2001 in the wake of an air quality conformity lapse that jeopardised the region's transportation funding. The rebirth of transit in 2014 and the success of the advocacy effort extends extant notions of urban regimes and governance in Atlanta and provides a unique example of a transportation equity win not forced by a legal challenge. Using primary and secondary source materials, this article illuminates precisely what made the Clayton County effort a success and looks to the future of public transit in the metropolitan region. While the precise conditions leading to MARTA's expansion are not likely to be replicated elsewhere, the work highlights the potential for coalitions composed of elected officials and non-profit organisations supported by philanthropic capital to make broad and lasting changes to regional transportation systems.